History of development and current state of comparative pedagogy - Chinibayeva, Gulnar; Berikkhanova, Aiman; Zhanar Seisenbayeva, Zhanalik Baltabayeva, Aiman Koblanova, (Opción, 2019)
The article aims to investigate the history of development and the current state of comparative pedagogy via the comparative-historical method. As a result, the features of the evolution of comparative pedagogy on the basis of retrospective analysis were determined; essential characteristics were established. In conclusion, particular importance is attached to overcoming terminological discrepancies. For example, different languages have different meanings of such concepts as „education‟, „secondary education‟, „higher education‟, etc.